Distribution and Sources of Oil Pollution Using Tar Balls as Indicator in Northeast Sumatra, Indonesia Via Fingerprinting Techniques - Sofia Anita, (2009)
Marine pollution due to oil spills in Northeast Sumatra, Indonesia had been started since Showa Maru spilled Middle East crude oil in 1975 and has become one of more severe environmental problem for this area and the Malacca Straits. The most polluted locations chosen were Aceh, North Sumatra, Riau and Riau Archipelago. This study presents fingerprinting and data interpretation used to characterize crude oils and tar balls in the Northeast Sumatra, Indonesia and a case study in of unknown spilled oil from Dumai coast. A variety of diagnostic ratios of molecular markers (i.e. n-alkanes, hopanes and polycyclic aromatic hydrocarbons; PAHs) were chosen to fingerprint them. The instrument used in this study was Gas Chromatography-Flame Ion Detector and Gas Chromatograph (GC) interfaced with Mass Selective Detector (MSD). Based on the objectives, the results reveal the following: (1) the origin of Minas, Duri, and Dumai crude oils is characterized by the diagnostic ratios of petroleum (i.e. unresolved complex mixtures, Pr/Ph ratio, carbon preference index (CPI), Tm/Ts ratio, the source identifiers of C29/C30 and ΣC31-C35/C30 ratio, MP/P ratio). The crudes were very likely due to the same basin, i.e., Central Sumatran Basin; (2) each tar ball has a different fingerprint and compound distribution. The tar balls found in Northeast Sumatra coasts are significantly different in the concentrations of PAHs. The ranges of polycyclic aromatic hydrocarbon levels (PAHs) vary from those low to very high petroleum contamination. Riau Archipelago coasts are found to be severe contaminated by PAHs originated from the spilled oil. The percentage of tar balls showed South East Asia Crude Oil, SEACO signature category to be 32%, Middle East Crude Oil, MECO 60%, and 8% from unknown sources (Bagan Siapi-Api and Batam tar balls). It is concluded that the sampling area in Northeast Sumatra might received spillage of waste petroleum product or used lubricating oil from multiple sources; (3) the spilled oil identified is the same as Dumai crude oil from Pertamina Refinery. The spills might be come from Pertamina Dumai refinery wash tank which took place in 2007.